Understanding Crime in Colombia and What Can Be Done About It - Levitt Steven
Abstract. We attempt to spell out the causes and costs of Colombia´s crime situation. Homicide rates are the highest in the world, three times higher than those of Brazil & Mexico and ten times higher than those of other Latin American countries. Paradoxically, Colombia is not exceptional with relation to property crime. In recent years, homicide rates have dropped in some of the most violent regions. Our conclusion is that drug trafficking coupled with low levels of punishment to criminals are the most important contributors to Colombian exceptional homicide rates. In relation to guerrillas, we find that their activities explain the high rates of kidnapping (and, in particular, its recent upsurge), but they are little related to the evolution of homicide rates. Socioeconomic factors, such as, income inequality and poverty, and sociological factors, such as the notion that Colombians are more violent by nature, do not appear to be the central explanation of crime rates in this country. Accordingly, our main policy recommendations are as follows: more and better information is required, lessening corruption in the criminal justice system is paramount, independent units for fighting kidnapping and homicides are needed, and financing the guerrillas so that they stop kidnapping should be explored. Most of our recommendations are related to the Colombian criminal justice system, the Plan Colombia and the drug policy.Violencia, Crimen, Economía Institucional, Reformas Institucionales